Antagonistic interaction between caffeine and ketamine in zebrafish: Implications for aquatic toxicity - Zhenglu Wang; Jindong Xu; Wei Du (Environmental Science and Ecotechnology)
The coexistence of caffeine (CF) and ketamine (KET) in surface waters across Asia has been widely reported. Previous studies have implied that CF and KET may share a mechanism of action. However, the combined toxicity of these two chemicals on aquatic organisms remains unclear at environmental levels, and the underlying mechanisms are not well understood. Here we demonstrate that KET antagonizes the adverse effects of CF on zebrafish larvae by modulating the gamma-aminobutyric acid (GABA)ergic synapse pathway. Specifically, KET (10–250 ng L−1) ameliorates the locomotor hyperactivity and impaired circadian rhythms in zebrafish larvae induced by 2 mg L−1 of CF, showing a dose-dependent relationship. Additionally, the developmental abnormalities in zebrafish larvae exposed to CF are mitigated by KET, with an incidence rate reduced from 26.7% to 6.7%. The competition between CF and KET for binding sites on the GABA-A receptor (in situ and in silico) elucidates the antagonistic interactions between the two chemicals. Following a seven-day recovery period, the adverse outcomes of CF exposure persist in the fish, whereas the changes observed in the CF + KET groups are significantly alleviated, especially with KET at 10 ng L−1. Based on these results, it is imperative to further assess the environmental risks associated with CF and KET co-pollution. This pilot study underscores the utility of systems toxicology approaches in estimating the combined toxicity of environmental chemicals on aquatic organisms. Moreover, the nighttime behavioral functions of fish could serve as a sensitive biomarker for evaluating the toxicity of psychoactive substances.